Rancang Bangun Sistem Monitoring Daftar Kehadiran Karyawan Berbasis Fingerprint dengan Metode Prototyping - Danistian, Angga; Darmawan, Budi; Rachman, A. Sjamsjiar (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Employee attendance issues are a significant concern in many organizations, particularly regarding fraudulent practices such as proxy attendance and data inaccuracies. Conventional attendance systems relying on signatures or ID cards are often ineffective in preventing these frauds. To address this issue, this study developed a fingerprint-based attendance system integrated with a database and website. The primary objective of this system is to facilitate the attendance recapitulation process, eliminate proxy attendance, and enhance employee awareness and discipline. This system uses fingerprint technology to ensure that each employee is physically present at the time of attendance, thereby improving the accuracy and reliability of attendance data. The research method used is experimental, involving the development of hardware and software with various interconnected components. The results show that this system not only simplifies attendance recapitulation but is also effective in preventing fraud, increasing employee awareness and discipline, and ensuring data security accessible only by the admin. Thus, the fingerprint-based attendance system proves to be an effective solution in addressing attendance issues in the workplace.